2016
DOI: 10.1080/15295192.2016.1158602
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Dysregulation Mediates Relations Between Chinese Parents’ Histories of Childhood Emotional Abuse and Parenting Stress: A Dyadic Data Analysis

Abstract: SYNOPSISObjective. This study focused on the intrapersonal and interpersonal effects of parents' histories of childhood emotional abuse and emotion dysregulation on parenting stress in a sample of school-age children's fathers and mothers in Mainland China. Design. One hundred ninety-four Chinese couples participated. Structural equation modeling within the framework of the actor-partner interdependence mediation model was used to assess whether emotion dysregulation mediates relations between parents' childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 74 publications
0
10
1
Order By: Relevance
“…Although there is evidence suggesting that fathers play an important role in family functioning, a paucity of family research has examined the experiences of fathers compared to those of mothers (e.g., Tomeny 2017; Zaidman-Zait et al 2018). However, fathers have an irreplaceable role in parenting, and there are differences between fathers and mothers in terms of the level of parenting they provide (Bai and Han 2016; Lee et al 2011). This might be especially true in families of children with ASD as autism is currently considered the developmental disability with the greatest impacts on the ordinary parenting role of fathers; having a child with autism leaves fathers significantly distressed, helpless, and vulnerable to many psychosocial problems (Lyons et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is evidence suggesting that fathers play an important role in family functioning, a paucity of family research has examined the experiences of fathers compared to those of mothers (e.g., Tomeny 2017; Zaidman-Zait et al 2018). However, fathers have an irreplaceable role in parenting, and there are differences between fathers and mothers in terms of the level of parenting they provide (Bai and Han 2016; Lee et al 2011). This might be especially true in families of children with ASD as autism is currently considered the developmental disability with the greatest impacts on the ordinary parenting role of fathers; having a child with autism leaves fathers significantly distressed, helpless, and vulnerable to many psychosocial problems (Lyons et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified links between child maltreatment and parenting problems including lower perceived competence (Bailey et al, 2012;Caldwell et al, 2011;Fitzgerald et al, 2005;Schuetze & Eiden, 2005), reductions in maternal sensitivity, responsivity, and empathy (Bert et al, 2009;Fuchs et al, 2015;Lyons-Ruth & Block, 1996;Pereira et al, 2012;Zvara, Meltzer-Brody, et al, 2017), increased use of harsh or physically punitive discipline (DiLillo et al, 2000;Schuetze & Eiden, 2005), and higher levels of hostile or intrusive behaviours (Bailey et al, 2012;Lyons-Ruth & Block, 1996;Moehler et al, 2007). Parents who were maltreated as children also exhibit inconsistent parenting behaviours (Collin-Vezina et al, 2005;Driscoll & Easterbrooks, 2007), and report higher levels of parenting stress (Bai & Han, 2016;Pereira et al, 2012).…”
Section: Child Maltreatment and Parenting Problemsmentioning
confidence: 99%
“…In addition to studies examining interactive effects of ES, some research has examined cross-over effects between spouses. For example, Bai and Han (2016) found that childhood emotional abuse experienced by one parent was positively associated with parenting stress in the other parent and determined that this relationship was mediated by the abused parent's emotional dysregulation. Similarly, Li and colleagues (2019) showed that higher levels of maternal emotion dysregulation predicted lower levels of supportive ES from fathers and indicated that this relationship was mediated by father's reports of marital conflict.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous studies have also shown a connection between parenting stress and both children's and parents' ER abilities (Deater-Deckard, Li, & Bell, 2016;Graziano et al, 2011;Mathis & Bierman, 2015). In one study, Bai and Han (2016) found that the ER abilities of a parent who was abused in childhood mediated his or her level of parenting stress as well as his or her partner's level of parenting stress.…”
Section: Parenting Stressmentioning
confidence: 95%
“…These benefits should extend to relationships with other family members as well, indirectly benefiting the identified child/children. Finally, strong ER skills may be a protective factor against parenting and family stress (Bai & Han, 2016).…”
Section: Caregiver Er Changes and Pcitmentioning
confidence: 99%